2005
DOI: 10.1577/a04-066.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Gonadal Development to Body Size and Plasma Sex Hormone Concentrations in Female Channel Catfish

Abstract: Most channel catfish Ictalurus punctatus do not spawn until age 3, which makes the process of genetic selection for desired characteristics time consuming. A simple method for identifying earlier-maturing fish would speed up the selection process. Two-and three-year-old females (U.S. Department of Agriculture [USDA]-103 strain) were used to correlate body weight and plasma sex hormone concentrations with gonadal development. We also examined the potential of reducing the time to maturation with exogenous estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…The secretion of estradiol during ovarian development stimulates vitellogenin synthesis in the liver. Vitellogenins are integrated into developing eggs as phosvitin and lipovitellin, resulting in increased ovarian size and GSI (Davis et al 2005). Data from this study similarly indicate the same progression with an increase in estradiol secretion followed by simultaneous increases in vitellogenin production and GSI.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The secretion of estradiol during ovarian development stimulates vitellogenin synthesis in the liver. Vitellogenins are integrated into developing eggs as phosvitin and lipovitellin, resulting in increased ovarian size and GSI (Davis et al 2005). Data from this study similarly indicate the same progression with an increase in estradiol secretion followed by simultaneous increases in vitellogenin production and GSI.…”
Section: Discussionsupporting
confidence: 66%
“…Hormones such as 17β-estradiol (estradiol) and testosterone have been used to assess reproductive development in multiple fish species (Zohar and Billard 1984, Foster et al 1993, Holcombe et al 2000, Davis et al 2005, Gross et al 2006, including members of the family Eleotridae (Wang et al 2001). Vitellogenin has been effective for determining onset of sexual maturation and its continued development in female teleosts, specifically by using an enzyme-linked immunosorbent assay (ELISA) (Jackson and Sullivan 1995, Heppell et al 1999, Gross et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of growth of ovary during vitellogenesis parallels those reported in other studies on rainbow trout (Tyler et al ) and indicates that considerable energy be required to complete this period of reproductive development. Davis et al () concluded that catfish at younger maturing ages had significant linear correlations between body weights and maturation indicators. Similarly, in this study, oocyte diameters and plasma vitellogenin levels of channel catfish females mimicked the gonadal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Moore (1986) showed that for older fish, as fish weight increased percent success of spawning and hatch percentage generally increased, and a similar trend was observed in younger fish, but data for the younger fish were not conclusive. Davis et al (2005) also suggested that age rather than size is a more important component of maturation. These authors proposed to expose fish to shortened seasonal changes that mimic increased age combined with intensive feeding of fish, as a solution to overcome age as a limiting factor in brood stock performance (Davis et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al (2005) also suggested that age rather than size is a more important component of maturation. These authors proposed to expose fish to shortened seasonal changes that mimic increased age combined with intensive feeding of fish, as a solution to overcome age as a limiting factor in brood stock performance (Davis et al 2005).…”
Section: Discussionmentioning
confidence: 99%